Aloe vera supplementation improves cardiovascular risk factors in hemodialysis patients: A randomized, double-blind, placebo-controlled trial - Akram Kooshki; Mohammad Reza Memarzadeh; Mohammad Hassan Rakhshani; Roya Akbarzadeh; Tahereh Tofighiyan; Elaheh Foroumandi (Mashhad University of Medical Sciences, 2024)
Objective: This study assessed the effects of Aloe verasupplementation on serum inflammatory factors, blood sugar andlipid profiles in hemodialysis patients.Materials and Methods: Totally, 50 hemodialysis patients wereallocated randomly to either Aloe vera or placebo groups. TheAloe vera group received 2 Aloe vera capsules daily for 8 weeks(500 mg/day). Serum C-reactive protein (hs- CRP), Fasting bloodglucose (FBS), and lipid profiles levels were evaluated at thebaseline and the end of the eighth week.Results: Aloe vera supplementation for 8 weeks was associatedwith a significant reduction of serum hs- CRP (p=0.004), totalcholesterol (p=0.01), low density lipoprotein (LDL) (p=0.02) levesand increased high density lipoprotein (HDL) (p=0.002)concentration in the hemodialysis patients.Conclusion: Aloe vera supplementation is beneficial inimprovement of cardiovascular risk factors in hemodialysispatients